Funcionamiento familiar v rendimiento académico en estudiantes de secundaria de la institución educativa 0292 – Tabalosos Marzo 2011 -y Abril 2012 - Carballo Shica, Gandy (2012)
The present qualified study: "Familiar Functioning and Academic Performance in Students of Secondary of the Educational institution N º 0292 - Tabalosos. March, 2011 - April, 2012 ", it had as aim: the existing relation identifies between the familiar functioning and the level of academic performance of the students of 4to and 5to degrees of the secondary level of the Educational institution N ° 0292 of Tabalosos's District, during the period between July, 2011 and July, 2012. The type of investigation raised was c;urrelacional and according to the compilation of the information of transverse type; 1 work with the design correlacional and the sample was shaped by 28 students and his families. To measure variable familiar functioning the questionnaire was in use as instrument " Since it is your Family " for the students and " Since it is his family " for the parents and to measure variable academic performance of the students there was in use the passbook of notes of the students. To interpret and to analyze the behavior of the variables in study the descriptive statistics was in use. The conclusions in the present study were: The level of vulnerability of the familiar functioning threw 57,1 % for level of average vulnerability, 32,1 % level of vulnerability of average to minor,7,1 % of average to major and 3,6 % in level of minor vulnerability. The general results of level of academic performance were 50,0 % level of academic low performance, 42,9 % academic average performance and 7,1 % high academic performance and a significant association did not exist between familiar functioning and the academic performance, of the students of the l. E. N º 0292, Tabalosos. March, 2011 - April, 2012.